Mutual influences between aphids on a joint host plant. - Müller, Fritz Paul; Steiner, Hanna (Contributions to Entomology = Beiträge zur Entomologie, 1991)
In view of the massing of one or more aphid species together on a single plant, the occurence of reciprocal effects may be anticipated. The proliferation of alatae in crowded colonies appears to be aconswquence and a means of avoiding intraspecific competition. Intraspecific competition involving physical aggression is known only for some Pemphigidae and Hormaphidinae. It is not uncommon for two aphid species to colonize the same plant together without exhibiting signs of interspecific competition. The higher nitrogen content of the plant tissue either induced directly by sucking or caused by galling may stimulate the settlement or growth even of another aphid species. A kind of allelopathy has been observed in special cases in which an immigrant aphid species or race dislodges another. Obviously, this mechanism is based on biochemical properties of the intruder’s saliva.